Protein intake and bone mineral density: Cross‐sectional relationship and longitudinal effects in older adults. Issue 1 (8th November 2022) - Groenendijk, Inge; Grootswagers, Pol; Santoro, Aurelia; Franceschi, Claudio; Bazzocchi, Alberto; Meunier, Nathalie; Caille, Aurélie; Malpuech‐Brugere, Corinne; Bialecka‐Debek, Agata; Pietruszka, Barbara; Fairweather‐Tait, Susan; Jennings, Amy; et al.
Abstract: Background: There are several mechanisms via which increased protein intake might maintain or improve bone mineral density (BMD), but current evidence for an association or effect is inconclusive. The objectives of this study were to investigate the association between dietary protein intake (total, plant and animal) with BMD (spine and total body) and the effects of protein supplementation on BMD. Methods: Individual data from four trials that included either (pre‐)frail, undernourished or healthy older adults (aged ≥65 years) were combined. Dietary intake was assessed with food records (2, 3 or 7 days) and BMD with dual‐energy X‐ray absorptiometry (DXA). Associations and effects were assessed by adjusted linear mixed models. Results: A total of 1570 participants [57% women, median (inter‐quartile range): age 71 (68–75) years] for which at least total protein intake and total body BMD were known were included in cross‐sectional analyses. In fully adjusted models, total protein intake was associated with higher total body and spine BMD [beta (95% confidence interval): 0.0011 (0.0006–0.0015) and 0.0015 (0.0007–0.0023) g/cm 2, respectively]. Animal protein intake was associated with higher total body and spine BMD as well [0.0011 (0.0007–0.0016) and 0.0017 (0.0010–0.0024) g/cm 2, respectively]. Plant protein intake was associated with a lower total body and spine BMD [−0.0010 (−0.0020 to −0.0001) and −0.0019 (−0.0034 to −0.0004) g/cm 2, respectively]. Associations were similar between sexes. Participants with a high ratio of animal to plant protein intake had higher BMD. In participants with an adequate calcium intake and sufficient serum 25(OH)D concentrations, the association between total protein intake with total body and spine BMD became stronger. Likewise, the association between animal protein intake with total body BMD was stronger. In the longitudinal analyses, 340 participants [58% women, median (inter‐quartile range): age 75 (70–81) years] were included. Interventions of 12 or 24 weeks with protein supplementation or protein supplementation combined with resistance exercise did not lead to significant improvements in BMD. Conclusions: An association between total and animal protein intake with higher BMD was found. In contrast, plant protein intake was associated with lower BMD. Research is warranted to further investigate the added value of dietary protein alongside calcium and vitamin D for BMD improvement, especially in osteopenic or osteoporotic individuals. Moreover, more research on the impact of a plant‐based diet on bone health is needed.